Lesions of the Parotid Gland and Buccal Artery After Buccal Fat Pad Reduction. Issue 3 (May 2019) - Vieira, Giovanni Modesto; Jorge, Fabrício David; Franco, Eduardo Jacomino; Dias, Leandro da Cunha; Guimarães, Maria do Carmo Machado; Oliveira, Laudimar Alves de
Abstract : Abstract: The significant increase in esthetic surgery, especially buccal fat pad reduction, has led to a corresponding increase in lesions and postoperatory after-effects from this surgical procedure. The aim of this study is to discuss the immediate and mediate risks of removing the Bichat ball, as well as describing a clinical study in which this surgical procedure resulted in lesions of the parotid gland and buccal artery, which was confirmed via nuclear magnetic resonance. The facial lesions were remedied via exploratory surgery by opening a new orifice of the glandular duct in the buccal cavity followed by drainage and compressive surgical bandages.